2022
DOI: 10.1371/journal.pone.0268751
|View full text |Cite
|
Sign up to set email alerts
|

A convenient online desalination tube coupled with mass spectrometry for the direct detection of iodinated contrast media in untreated human spent hemodialysates

Abstract: Background Mass spectrometry (MS) analysis using direct infusion of biological fluids is often problematic due to high salts/buffers. Iodinated contrast media (ICM) are frequently used for diagnostic imaging purposes, sometimes inducing acute kidney injury (AKI) in patients with reduced kidney function. Therefore, detection of ICM in spent hemodialysates is important for AKI patients who require urgent continuous hemodiafiltration (CHDF) because it allows noninvasive assessment of the patient’s treatment. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…LC-MS/MS is useful to compare the changes in serum protein profiles between low-flux and high-flux HD [22]. LC-MS/MS can assess the efficacy of protein removal from dialyzer membranes by analyzing toxic substances [23,24] and unintentionally lost proteins[25]. In this study, by using mass spectrometric analysis, we first showed that the PMMA membrane exhibited significantly higher adsorption of β2-MG, dermcidin, and immunoglobulin λ-1 light chain.…”
Section: Discussionmentioning
confidence: 99%
“…LC-MS/MS is useful to compare the changes in serum protein profiles between low-flux and high-flux HD [22]. LC-MS/MS can assess the efficacy of protein removal from dialyzer membranes by analyzing toxic substances [23,24] and unintentionally lost proteins[25]. In this study, by using mass spectrometric analysis, we first showed that the PMMA membrane exhibited significantly higher adsorption of β2-MG, dermcidin, and immunoglobulin λ-1 light chain.…”
Section: Discussionmentioning
confidence: 99%